1983
DOI: 10.1210/endo-113-6-2299
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Insulin Levels Are Elevated in the Cerebrospinal Fluid of Genetically Obese Zucker Rats

Abstract: Immunoreactive insulin (IRI) concentrations were measured in plasma and cerebrospinal fluid (CSF) of four-month old genetically obese Zucker rats, their heterozygote lean littermates, and age-matched normal-weight Wistar rats. Basal plasma IRI was 201 + 35 microU/ml (means +/- SEM) in the obese animals and was significantly elevated compared to both lean Zucker rats (18 +/- 2.4 microU/ml, P less than 0.001) and Wistar rats (12 +/- 2.4 microU/ml, P less than 0.001). The mean CSF IRI concentration of fasted obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 9 publications
4
18
0
Order By: Relevance
“…There are numerous reports of increased fasting plasma insulin (19,49,50); similar observations have been made in CSF of animal models of obesity (51,52). Circulating levels of insulin were relatively low in all groups, presumably due to a combination of the isoflurane-mediated suppression of insulin release (53) and the fasted state of the animals.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…There are numerous reports of increased fasting plasma insulin (19,49,50); similar observations have been made in CSF of animal models of obesity (51,52). Circulating levels of insulin were relatively low in all groups, presumably due to a combination of the isoflurane-mediated suppression of insulin release (53) and the fasted state of the animals.…”
Section: Discussionsupporting
confidence: 67%
“…Consistent with our data on obese rats, insulin levels in the CSF have previously been reported to be elevated in obese rats (52), sheep (54), and humans (55). Although this appears inconsistent with a recent report on humans (56), that group reported only ratios of plasma to CSF insulin without presenting the actual levels of insulin in the CSF.…”
Section: Discussionsupporting
confidence: 59%
“…In the mid-1950s, two studies described an inability of radioactively labeled insulin, injected in the periphery, to be detected in the brains of human or dogs (Elgee, Williams, & Lee, 1954;Haugaard, Vaughan, Haugaard, & Stadie, 1954). However, studies in the 1970s demonstrated that insulin was found in the CSF of numerous species (Stein et al, 1983;Woods & Porte, 1977). From these studies, important characteristics were identified including a strong relationship between the peripheral levels of insulin and levels in the CSF and a limit to the increase of CSF insulin when plasma insulin was at supraphysiological levels.…”
Section: Transport Of Insulin Into the Cnsmentioning
confidence: 99%
“…The process is saturable, selective for insulin, and regulated (39 -42). Insulin transport into the brain is reduced during fasting (43), by maintenance on a high-fat diet (44), and in genetic and dietary-induced obesity (45,46). Because brain insulin derives from plasma insulin, it should be the case that experimentally induced increases of plasma insulin enter the brain and result in reduced food intake and body weight.…”
Section: Insulin As An Adiposity Signalmentioning
confidence: 99%